2004
DOI: 10.1128/aac.48.12.4556-4561.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CTX-M-Type β-Lactamase Genes in Fecal Escherichia coli Isolates from Healthy Children in Bolivia and Peru

Abstract: A survey was carried out from August to November 2002 to evaluate the antimicrobial susceptibilities of fecal Escherichia coli isolates from 3,208 healthy children from four different urban areas of Latin America, two in Bolivia (Camiri and Villa Montes) and two in Peru (Yurimaguas and Moyobamba). Ceftriaxone-resistant E. coli isolates were detected in four children, one from each of the areas sampled. The isolates exhibited a multidrug-resistant phenotype, including resistance to oxyimino-cephalosporins and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 35 publications
2
53
2
4
Order By: Relevance
“…In contrast, they differ from those obtained in children from Asia and South America (28,29) and particularly from those obtained in the North American pediatric study by Chandramohan et al (30), who found 60% bla CTX-M-15 , 14.3% bla CTX-M-14 , and 2.1% bla CTX-M-27 ESBLs. In addition, CTX-M diversity was higher in our study, with the presence of CTX-M-1, -14, -15, -3, -2, -27, and -57 (28)(29)(30).…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast, they differ from those obtained in children from Asia and South America (28,29) and particularly from those obtained in the North American pediatric study by Chandramohan et al (30), who found 60% bla CTX-M-15 , 14.3% bla CTX-M-14 , and 2.1% bla CTX-M-27 ESBLs. In addition, CTX-M diversity was higher in our study, with the presence of CTX-M-1, -14, -15, -3, -2, -27, and -57 (28)(29)(30).…”
Section: Discussioncontrasting
confidence: 51%
“…Amplicons were sequenced on both strands at an external facility (Macrogen Inc., Seoul, South Korea), and the deduced protein sequences were compared with those available in the GenBank database by using the BLAST program (http://blast.ncbi.nlm.nih.gov). The presence of bla CTX-M , bla OXA-9 , bla SHV , bla TEM , bla IMP , bla VIM , and bla KPC ␤-lactamase genes was investigated using primers and methods described previously (26)(27)(28)(29).…”
Section: Fig 1 Evolution Of the Outbreak Caused By Esc-resistant K Pmentioning
confidence: 99%
“…According to several recent publications, E. coli isolates producing extended-spectrum ␤-lactamases (ESBL) of the CTX-M type have emerged in the community in numerous countries (25)(26)(27)(28). These isolates resist extended-spectrum cephalosporins because of CTX-M production and are often resistant to other antibiotic families, in particular fluoroquinolones and/or cotrimoxazole (28).…”
mentioning
confidence: 99%